SPIRITUALITAS DAN TEOLOGI SOSIAL PENTAKOSTAL ASIA - Anggi Maringan Hasiholan (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Asia is a locus of a society full of suffering and poverty. An active role in social life is an expected construction for the relevance of life. The article examines the spirituality and theology adopted by Pentecostals to engage in social life. The research method used is qualitative with a constructive theology approach. The research results show that the relationship between creation and history becomes essential because it provides a way to talk about the importance of action in the divinely created biophysical order while still distinguishing it from the discussion about creation as a product of divine causality. The maintenance of the Holy Spirit in creation is done with involvement in responding to social issues. When one understands creation as a biophysical order, the created order contains development in mind. In other words, the cultural mandate reflects the implicit understanding that the entire biophysical order was created in a potential state, ready for a long development process, and maintained with the help of the Holy Spirit.